Introduction to the Special Issue on Sexting - Selinger, Eric Murphy (Journal of popular romance studies, 2022)
When Eftihia Mihelakis and Jonathan A. Allan first called for papers on “Sexting, Romance, and Intimacy,” they cast a wide net, inviting submissions on the many ways in which sexting has become a part of popular culture, whether as a cautionary tale or as a neutral or even quite positive part of contemporary “lover’s discourse.” They defined sexting quite broadly—from flirtatious and / or loving text messages to the nefarious world of unsolicited dick pics and the violence of revenge porn. They noted sexting’s ubiquity in film, television, the novel, the six o’clock news, and as part of middle and high school curricula; and they hoped to begin an equally expansive conversation about the phenomenon, one that would take into account a history dating back at least to the Polaroids of decades past, the rise of the personal camcorder, and the invention of the sex tape, and which could thereby bring ostensibly disparate acts and texts into productive conversation. (“How might we think about a film like You’ve Got Mail in relation to the Netflix series, You, or to the emails exchanged in Fifty Shades of Grey?” they wondered, for example.)As often happens with an expansive call for papers, the submissions we received addressed only a portion of these possible topics. Rather than exploring representations of sexting in fiction, film, and TV, they focused on sexting as a real-world romantic behavior. Indeed, of the three papers that make up this special issue, two are situated squarely within the social sciences. Drawing on questionnaire responses, Samantha F. Quinn and Arrington Stoll’s essay “An Exploration of Sexting as a Form of Infidelity in Consensually Non-Monogamous Relationships” documents why non-dyadic romantic partners sext outside their relationships and “what constitutes ‘crossing the line’” when such sexting occurs. In “The Interactions of Risk, Trust, and Permanence on Individuals’ Motivations for Sexting,” Jessica A. Kahlow and Elizabeth M. Jenkins analyze how “individuals’ motivations for sending sexts are influenced by trust, risk, and message permanence,” situating their analysis in the theoretical / practical context of Communication Privacy Management. Only the final paper, “Reading the Dick Pic Reparatively,” by Andrea Waling, Frank G. Karioris, and Jonathan A. Allan, places itself primarily (though not exclusively) within the humanities, drawing on Eve Kosofsky Sedgwick and other queer theory to reframe discussions of the dick pick around “questions of desire, intimacy, the erotic, and vulnerability.”Rather than speaking any sort of last word on the subject of sexting, then, we at JPRS see this special issue as only a first small step towards understanding it as lived practice, plot device, and compositional tactic. Indeed, by an accident of history, the Call for Papers for this special issue closed only weeks before the technological mediation of intimacy became, for many, a matter of daily necessity in Spring 2020. As Ania Malinowska explains, “When COVID-19 put half of the globe under lockdown, transmission media took over most of our emotional (and other) interactions,” such that “traditional axioms of encounter—that of the mode (face-to-face), locus (restaurant, hotel) and temporality (natural/analogue time; social time)—were almost completely replaced by their digital counterparts, and on a global scale” (2). The essays in this issue are thus valuable not only in their own right, but also as instigations and frameworks for future research on the subject of sexting, both on its own and as a feature of what Malinowska calls “love in contemporary technoculture.” We are very happy to present them to our readers, and we are eager to see the scholarship that they inform and inspire.Works CitedMalinowska, Ania. Love in Contemporary Technoculture. Cambridge UP, 2022.